Changing big business the globalisation of the fair trade movement - Hutchens, Anna.; Edward Elgar Publishing (Cheltenham, U.K. : Edward Elgar, 2009)
Drawing on candid accounts from practitioners, producers and industry representatives, this informative and proactive volume investigates the challenges facing today's fair trade movement and provides unique insights into the workings of social and economic power in world markets.
1. 'Game-playing': rethinking power and empowerment -- 2. 'Power over' as global power in world markets -- 3. The history of fair trade -- 4. Networking networks for scale -- 5. Fairtrade as resistance -- 6. Fair trade as game-playing -- 7. Governance as 'creative destruction'.
Includes bibliographical references (p. 210-228) and index.
Keywords: Free trade; Anti-globalization movement; Globalization -- Economic aspects; Electronic books